Climate change has increased the odds of extreme regional forest fire years globally - John T. Abatzoglou; Crystal A. Kolden; Alison C. Cullen; Mojtaba Sadegh; Emily L. Williams; Marco Turco; Matthew W. Jones (Nature Communications)
Abstract Regions across the globe have experienced devastating fire years in the past decade with far-reaching impacts. Here, we examine the role of antecedent and concurrent climate variability in enabling extreme regional fire years across global forests. These extreme years commonly coincided with extreme (1-in-15-year) fire weather indices (FWI) and featured a four and five-fold increase in the number of large fires and fire carbon emissions, respectively, compared with non-extreme years. Years with such extreme FWI metrics are 88-152% more likely across global forested lands under a contemporary (2011–2040) climate compared to a quasi-preindustrial (1851–1900) climate, with the most pronounced increased risk in temperate and Amazonian forests. Our results show that human-caused climate change is raising the odds of extreme climate-driven fire years across forested regions of the globe, necessitating proactive measures to mitigate risks and adapt to extreme fire years.